PSYCHOPHYSIOLOGIC AND IMMUNOLOGIC CHARACTERISTICS IN PATIENTS WITH BRONCHIAL ASTHMA AND IN HEALTHY MEN WITH DIFFERENT FUNCTIONAL ASYMMETRY OF THE HEMISPHERES OF THE BRAIN - A. V. Smyk (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
On the basis of the analysis of own and literary data, proved the interaction psychophysiologic and immunologic parameters in healthy people and in patients with bronchial asthma. The main accent was made on the investigation of the role of the functional asymmetry of a brain, as the base phenomenon defining features of mental, vegetative and immunologic activity.